Abuse of the Implementation of the General Meeting of Shareholders by the Commissioners and the Legal Consequences of the Deed of Statement of Meeting Resolution made by the Notary - Mutiara, Arini; Mekka Putra, Mohamad Fajri (Sahabat Publikasi, 2025)
The General Meeting of Shareholders (GMS) serves as a decision-making mechanism within a Limited Liability Company (LLC) and plays a crucial role; however, it is often utilized as a tool for personal or specific group interests, leading to abuses in the conduct of GMS procedures. This research aims to analyze the legal mechanisms that determine the validity of changes within the company through the organization of the GMS, as well as the legal accountability in cases of abuse of the General Meeting of Shareholders (GMS) by Commissioners and the legal consequences for the minutes of meeting decisions made by a Notary, as explained in Case Decision Number 214/Pdt.G/2021/PN Jkt.Utr.This study employs a normative juridical method with a descriptive-analytical research typology. In this context, the abuse of GMS execution by Commissioners or related parties that harms other shareholders or third parties will be analyzed within the framework of unlawful acts. The results of this study indicate that the validity of changes within the company through the execution of the GMS heavily relies on clear meeting call procedures, qualified quorum, shareholder approval, and endorsement by the Ministry of Law and Human Rights, as stipulated in the company's Articles of Association and relevant laws concerning Limited Liability Companies. Legal accountability and legal implications for the minutes of meeting decisions made by a Notary become invalid and non-binding due to changes in the company's structure—whether in terms of amendments to the Articles of Association, share transfers, or changes in management composition—because they are not based on compliance with the Company Law (UUPT) and the company's Articles of Association. This provides an opportunity for aggrieved parties to file civil lawsuits or criminal charges.